Audit Quality, CEO Ownership, and Earnings Management: An Empirical Analysis of Listed Non-Financial Services Firms in Nigeria - Efiong, Eme Joel, PhD; Ibrahim Mallam Fali, PhD; Ogar- Abang, John Oyong, PhD; Animpuye Canice; Adamu Haruna Sezuo; Oboh John Ogenyi; Umagu Udemeobong Bahakongfe (International Journal of Economics, Business and Innovation Research, 2025)
The primary objective of this study was to examine the moderating effect of Chief Executive Officer (CEO) share ownership on the relationship between audit quality and earnings management in Nigeria’s listed non-financial services firms, covering the period from 2013 to 2022. A sample of 72 firms was selected, with real earnings management employed as the proxy for the dependent variable. The study adopted a correlational and ex post facto research design, utilizing secondary data obtained from firms’ annual reports and the Nigerian Exchange Group website. Descriptive statistics and panel multiple regression analyses were conducted, with the random effects model and generalized least squares estimation applied for robustness. The findings reveal that audit quality has a negative and significant effect on earnings management, while CEO share ownership exerts a positive and significant effect. However, the moderated regression model indicates that CEO share ownership does not significantly moderate the relationship between audit quality and earnings management. The study concludes that CEO ownership levels do not influence how audit quality mitigates earnings management in Nigeria’s non-financial sector. Consequently, it recommends that regulatory efforts to curb earnings management should prioritize strengthening external audit quality and enforcing rigorous audit standards, rather than relying on CEO ownership structures as a corporate governance mechanism. Firms are advised to consistently maintain high audit quality standards to enhAdd Contributorance the credibility of financial reporting irrespective of CEO ownership levels.